Active compounds and biological activities of geranium aralia (Polyscias guilfoylei (W. Bull) L.H. Bailey) leaf extract against larval stage of melon fly (Zeugodacus cucurbitae Coquillett) - Rachmawati, Jeti; Martono, Edhi; Trisyono, Y. Andi (Kasetsart University Research and Development Institute, 2022)
Importance of the work: Polyscias guilfoylei is a shrub that is known as a medicinal plant whose leaf extracts contain active compounds, such as saponins. Objectives: To determine the active compounds and biological activities of P. guilfoylei leaf extracts against Zeugodacus cucurbitae. Materials & Methods: The research was conducted in the Plant Pest Laboratory using a randomized block design arranged in a factorial manner. The solvents used were ethanol and n-hexane at concentrations of 0%, 1.25%, 2.50% and 5.00%. All treatments were replicated four times. The parameters observed were: active compound content, larval feeding and growth activities. Results: Ultraviolet-visible spectrophotometry and thin layer chromatography indicated that the ethanol P. guilfoylei leaf extracts contained phenols, tannins, alkaloids, flavonoids and saponins, while the n-hexane P. guilfoylei leaf extracts contained terpenoids, steroids, phenols, tannins, alkaloids, flavonoids and saponins. Application of 5.00% ethanol or n-hexane P. guilfoylei leaf extracts caused lower values for feeding activity and the feeding deterrent index. In addition, the extracts affected larval and pupal periods, the number of larvae reaching pupation and the pupal weight of Z. cucurbitae. Application of higher concentrations of extracts resulted in longer larval and pupal periods, a reduced pupal weight and fewer larvae reaching the pupal stage. Main finding: The active compounds in P. guilfoylei leaf extracts were phenols, tannins, alkaloids, flavonoids and saponins. Application of leaf extract at up to 5.00% could deter larval feeding and the growth activities of Z. cucurbitae.